━━━━━━━☆☆━━━━━━━
▹ Answer
<em>4 ÷ 2/3 = 6</em>
<em>1 ÷ 10/3 = 3/10</em>
<em>1 ÷ 4/7 = 1 3/4</em>
<em>9 ÷ 1/3 = 27</em>
<em>4 ÷ 5/4 = 3 1/5</em>
▹ Step-by-Step Explanation
4 ÷ 2/3 = 4 × 3/2 = 12/2 = 6
1 ÷ 10/3 = 1 × 3/10 = 3/10
1 ÷ 4/7 = 1 × 7/4 = 7/4 = 1 3/4
9 ÷ 1/3 = 9 × 3/1 = 27/1 = 27
4 ÷ 5/4 = 4 × 4/5 = 16/5 = 3 1/5
Hope this helps!
- CloutAnswers ❁
Brainliest is greatly appreciated!
━━━━━━━☆☆━━━━━━━
Answer:
the answer is B because 3(x-2) is the same as 3x -2
Answer:
The additive inverse of (-12) is 12
Step-by-step explanation:
You know that the absolute value of 12 is 12 so this can be verified by: 12 +(- 12) = 0. Hope this helps!
Bjsjshshsjssdddjbhhdgehhee